2017
DOI: 10.3996/122015-jfwm-124
|View full text |Cite
|
Sign up to set email alerts
|

Lead Poisoning in Bald Eagles Admitted to Wildlife Rehabilitation Facilities in Iowa, 2004–2014

Abstract: Eleven years (2004–2014) of bald eagle Haliaeetus leucocephalus data from four independent, state and federally permitted wildlife rehabilitators in Iowa were assessed for the prevalence of elevated lead levels in blood or tissue samples. The relationship between blood lead concentrations and recorded information (age, season, radiographs, and clinical outcome) was investigated. Adult birds had higher blood lead concentrations than immature and juvenile birds. Highest blood lead levels were found during Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The proportion of lead-poisoned eagles increased in all 4 migratory bird flyways of the United States after the autumn 1991 ban on the use of lead shot for waterfowl hunting, probably as Bald Eagles consume lead ammunition fragments (from bullets) in offal and carcasses left behind during big game hunting seasonsRussell and Franson (2014)USA—Iowa31% of 209 eagles brought to rehabilitation centres (2004-2014) had PbB > 60 µg/dl. 30 of 59 birds for which livers were analysed post-mortem had liver Pb > 6.0 ppm ww, suggestive of clinical poisoningYaw et al (2017)USA—Iowa, Minnesota and WisconsinCanada—Ontario38% of 58 birds found had liver Pb > 6 ppm ww. Birds were from areas where 36% of discarded offal piles from hunter-killed deer were found to contain lead fragments.Warner et al (2014)23% (10/43) of birds found dead and dying between 1991 and 2008 died of lead poisoningMartin et al (2018)Steller’s sea eagle Haliaeetus pelagicus Hokkaido, Japan18 of 43 dead birds collected after a ban on the use of lead bullets for hunting sika deer had elevated liver lead concentrations (> 2 ppm w.w.) associated with poisoning.…”
Section: Pathways Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of lead-poisoned eagles increased in all 4 migratory bird flyways of the United States after the autumn 1991 ban on the use of lead shot for waterfowl hunting, probably as Bald Eagles consume lead ammunition fragments (from bullets) in offal and carcasses left behind during big game hunting seasonsRussell and Franson (2014)USA—Iowa31% of 209 eagles brought to rehabilitation centres (2004-2014) had PbB > 60 µg/dl. 30 of 59 birds for which livers were analysed post-mortem had liver Pb > 6.0 ppm ww, suggestive of clinical poisoningYaw et al (2017)USA—Iowa, Minnesota and WisconsinCanada—Ontario38% of 58 birds found had liver Pb > 6 ppm ww. Birds were from areas where 36% of discarded offal piles from hunter-killed deer were found to contain lead fragments.Warner et al (2014)23% (10/43) of birds found dead and dying between 1991 and 2008 died of lead poisoningMartin et al (2018)Steller’s sea eagle Haliaeetus pelagicus Hokkaido, Japan18 of 43 dead birds collected after a ban on the use of lead bullets for hunting sika deer had elevated liver lead concentrations (> 2 ppm w.w.) associated with poisoning.…”
Section: Pathways Of Exposurementioning
confidence: 99%
“…Recent studies illustrate that some partial bans on the use of lead ammunition do little to reduce lead poisoning mortality in raptors and scavengers. In North America, lead poisoning continues to be a significant cause of mortality in bald and golden eagles, despite the ban in autumn 1991 on the use of lead ammunition for shooting waterfowl (Russell and Franson 2014; Warner et al 2014; Yaw et al 2017). This is largely because eagles consume lead bullet fragments in offal and carcasses left behind during big game hunting.…”
Section: Impacts Of Lead Poisoning On Wildlifementioning
confidence: 99%
“…Despite 3 decades of a lead ammunition ban for waterfowl hunting, effects of lead poisoning from hunting ammunition persist. For example, bald eagle populations are increasing and no longer endangered (Millsap et al ), but dead and moribund birds resulting from lead ammunition exposure are routinely found (Bedrosian et al , Yaw et al ). During 2012, 58 dead bald eagles were collected across Iowa, Minnesota, and Wisconsin, USA, with 60% of the birds showing detectable lead concentrations from consumption of white‐tailed deer ( Odocoileus virginianus ) gut piles containing lead bullet fragments (Warner et al ).…”
Section: Past and Present Issuesmentioning
confidence: 99%
“…During 2012, 58 dead bald eagles were collected across Iowa, Minnesota, and Wisconsin, USA, with 60% of the birds showing detectable lead concentrations from consumption of white‐tailed deer ( Odocoileus virginianus ) gut piles containing lead bullet fragments (Warner et al ). Additional research has demonstrated extensive bald eagle mortality resulting from ingestion of lead bullet fragments in deer (Cruz‐Martinez et al , Franson and Russell , Golden et al , Yaw et al ).…”
Section: Past and Present Issuesmentioning
confidence: 99%
“…Despite three decades of a lead ammunition ban for waterfowl hunting, the effects of lead poisoning from hunting ammunition persists. For example, bald eagle populations are increasing and no longer endangered (Millsap et al, 2016), but dead and moribund birds resulting from lead ammunition exposure are routinely found (Bedrosian et al, 2012;Yaw et al, 2017). During 2012, 58 dead bald eagles were collected across Iowa, Minnesota, and Wisconsin with 60% of the birds showing detectable lead concentrations from consumption of white-tailed deer (Odocoileus virginianus) gut piles containing lead bullet fragments (Warner et al, 2014).…”
Section: Past and Present Issuesmentioning
confidence: 99%